Direct and alternating currents : - Loew, E. A. (McGraw-Hill, 1954)
The aim of this book as set forth in the preface to the first edition remains unchanged. It is to provide a single-volume text covering circuit theory and machinery of direct and alternating currents that is suitable as a text in a first course for majors in electrical engineering and in survey courses for majors in all other branches of engineering.